DETERMINAÇÃO DE METAIS EM TILÁPIA (Oreochromis niloticus), ÁGUA E SEDIMENTO DE UM RESERVATÓRIO NA CIDADE DE PONTA GROSSA- PR E AVALIAÇÃO TOXICOLÓGICA POR ESTUDO DE ESTRESSE OXIDATIVO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The present work determined to evaluate the impact of potentially toxic metals in the lake of Ponta Grossa - PR and quantified through the atomic absorption spectrometry. To identified the concentration of metals such as Cd, Co, Cr, Cu, Mn, Ni, Pb and Zn in water, sediment, Oreochromis niloticus muscle, liver of fish. Moreover also determined the impact of metals in fish's liver by the study of oxidative stress. In all water samples were determined that, the presence of Co, Mn and Ni metals in a dissolved fraction. In the sediment met for metals concentrations ranging from 4.6 ± 0.9 to 865.5 ± 38.2 mgKg-1. The observed concentrations of Cd (4,6±0,9 mgKg-1), Cu (141,9±5,1 mgKg-1) and Pb (53,4±6,6 mgKg-1) represented that, the potential danger to exposed organisms, nevertheless the results were between the index TEL (threshold effect level) and PEL (probable effect level). In fact, Zn metal showed concentration above PEL indicated that, it can be directly related to the adverse biological effects. In addition, Ni(5,4±0,4 mgKg-1) and Pb (24,4±2 mgKg-1) metals concentration in Oreochromis niloticus muscle were above the value stipulated by ANVISA (Ni - 5,0 mgKg-1, Pb – 0,3 mgKg-1) for human consumption suggested, the contamination of the species as well as a risk to human's health when they consume these fish. Moreover, potentially toxic metals concentration in the liver was higher than the concentration observed in muscle indicated that, the greater affinity between metals and liver than the metals and muscle. Such fact was confirmed by the bioaccumulation factor, once the values of liver were higher than the values of muscle. Both the liver (89,52±2,59 mgKg-1) and muscle (33,4±6,9 mgKg-1) showed highest concentration of Zn metal. This concentration was increased in the sediment revealed that, the contamination of fish occurred due to the contact with sediment. Apart from these, the biological data showed that, increased levels of lipid peroxidation, carbonylation protein and increased in GSH and the ratio by Hierarchical Cluster Analysis (HCA) of metals metallothionein (MT).Based on the above, concluded that, the metals contaminants the water and sediment. Besides, the metals has negatively influence on the Oreochromis niloticus species from lake.
Keywords: determinação de metais; Tilápia; estresse oxidativo; metal determination; Tilapia; oxidative stress; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA